4-(sec-butylamino)-3-nitrobenzoic acid - Narendra Babu, Shivanagere Nagojappa; Abdul Rahim, Aisyah Saad; Abd Hamid, Shafida; Yeap, Chin Sing; Fun, Hoong-Kun (International Union of Crystallography, 2009)
The asymmetric unit of title compound, C11H14N2O4, consists of two crystallographically independent molecules (A and B). In each, intramolecular N-H...O hydrogen bonds generate S(6) ring motifs. The mean plane of the nitro group forms dihedral angles of 4.5 (3) and 0.5 (3)° with the benzene ring in molecules A and B, respectively. In molecule A, there is disorder of the butylamino group which corresponds to an approximate 180° rotation about the N-C(H) bond, forming two sites with refined occupancies of 0.722 (6) and 0.278 (6). Molecule B is similarly disordered but in addition there is further rotational disorder about the C(H)-C(H2) bond giving a ratio of occupancies for three components of 0.42:0.35:0.23. In the crystal structure, intermolecular O-H...O hydrogen bonds link molecules into centrosymmetric dimers generating R22(8) ring motifs. The crystal structure is also stabilized by weak intermolecular C-H...O interactions.